Valorisation of Pulp and Paper Mill Sludge by Hydrothermal Carbonisation - Chirwa, Evans M.N. (University of Pretoria, 2022)
Dissertation (MSc Applied Science (Water Utilisation))--University of Pretoria, 2021.